IMPLEMENTASI DIGITALISASI REKAM MEDIS UNTUK MENDUKUNG REKAM MEDIS ELEKTRONIK - Mulyana; Masriani Situmorang; Siti Wulandari (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
The development of the digital era has highlighted the importance of integrating routine and high-quality data as part of the digital transformation process. One crucial data component that needs to be maintained is the Electronic Medical Record (EMR). Puskesmas Baloi Permai is currently piloting the implementation of EMR and requires technical assistance in digitizing paper-based medical records into electronic form. Digitization is necessary to ensure the continuity of patients' medical history information. This effort aims to support the successful implementation of EMR at Puskesmas Baloi Permai. Solutions are implemented to address the partner's challenges through training and the transfer of knowledge and technology. Training activities involve counseling and demonstrations. The knowledge and technology transfer in Puskesmas Baloi Permai entails introducing new methods and technologies for digitizing medical records and replacing outdated practices. The activities are divided into two stages: initially, a presentation is given on the procedures for digitizing electronic medical records, followed by discussions on the digitization process. To ensure the success of medical record digitization, demonstrations are conducted, including sorting the medical record forms to be scanned, simulating the scanning process, saving files for easy identification, and importing image files into the EMR system through appropriate media.